Epistylia Ice Cream Entreprise / Asyraf Ahmad Badri... [et al.] - Ahmad Badri, Asyraf; Zuber, Aienie Zubaidah; Othman, SitiNoor Masita; Norashikin, Siti Nor Izzaty (2012)
Ice cream is a very famous food product. People will still buy ice cream at any time and any season of the year. Malaysia is an equator country. Malaysia is hot and humid all year round and because of that opening an ice cream business is good. Four brilliant youngsters decided to planning start an ice cream enterprise namely Epistylia Ice Cream’. After doing some research in the districts of Langkawi, we found out that there is high demand for ice cream shop in Langkawi generally. Then we discovered Pantai Chenang as a good location to start our ice cream business. Epistylia is a company that has its own specialty. The word ‘Epistylia’ means topping this explains that Epistylia is an ice cream company that focuses on toppings of ice cream. Epistylia Ice Cream is located at Pantai Chenang, Langkawi. This location was chosen because it as one of the greatest tourist attraction of Langkawi. Pantai Chenang is usually crowded with tourists from morning till late night; everyday of the week, this geographical condition makes it a good location to start our business. Furthermore, there is no other established ice cream business opened in Pantai Chenang until now. Epistylia Ice Cream offers 100 types of toppings which consist of crunchies, gummies, and fruit. There are 10 categories of toppings. For example, one of the categories is fruits toppings and under fruit toppings we have pineapples, bananas, honeydews strawberries, cranberries and more. In addition, other unique feature of Epistylia Ice Cream is that our product is sold using a modified lorry. The lorry is designed and modified to become our moving shop according to particular layout and arrangements. The lorry or our moving shop will move very slowly across Pantai Chenang to attract customers. Within the lorry, all our ice creams and toppings are well viewable to customers for them to choose wisely.